P04.06 Partner number and outcomes of partner notification among gay, bisexual, and other men who have sex with men with infectious syphilis in british columbia, canada. (13th September 2015) - Wong, J; Achen, M; Holgerson, N; Ogilvie, G; Gilbert, M
Abstract : Background: Since 2010, infectious syphilis (IS) cases in British Columbia (BC) have increased 4-fold among gay, bisexual, and  other men who have sex with men (MSM). In BC, all syphilis cases and partner notification (PN) are managed centrally. We describe trends in PN outcomes from 2010–2013. Methods: We conducted chart reviews on a random sample (n = 350) representing 33% (350/1054) of all IS cases among MSM in BC from 2010–2013. We described trends in number of anonymous and notifiable partners, proportions notified and tested, and test outcomes. Results: The 350 cases (44% primary/secondary, 56% early latent) reported 1942 partners; 1131 (58%, range 46–67%) partners were notifiable. From 2010–2013, the number of partners per case increased (average 5 to 8; 6% to 16% reported ≥10 partners). Of the 1131 notifiable partners, 936 (83%) were notified: 638 (56%) by the case, 252 (22%) by a healthcare provider (HCP), and 46 (4%) by other means (e.g., referred to another jurisdiction). From 2010–2013, the proportion of case-notified partners was stable while the proportion of HCP-notified partners decreased (43% to 19%). Of the 936 partners notified, 287 (31%) were known to be tested (21% [133/638] of case-notified and 54% [135/252] of HCP-notified partners). Of these, 62 (22%) partners tested positive and were treated. From 2010–2013, the proportion of partners known to be tested decreased, primarily due to a decrease among case-notified partners (46% to 15%). Conclusion: Overall 83% of notifiable partners were notified. Challenges to PN among MSM in BC include anonymous partners, the increasing number of partners to be notified, and documentation of outcomes for case-notified partners. While self-notification appears to be preferred by many MSM, partner testing may be lower in this group. Strategies to encourage partner testing (whether case or HCP-notified) are needed and may be best focused on MSM with more partners. Disclosure of interest statement: The BC Centre for Disease Control is a provincial public health agency which has a responsibility for surveillance of communicable diseases, including HIV and sexually transmitted infections. No external funding was received for this study. All authors have no conflicts of interest.